Development and validation of the MISSCARE survey – Pediatric version. (24th September 2018) - Bagnasco, Annamaria; Zanini, Milko; Aleo, Giuseppe; Catania, Gianluca; Kalisch, Beatrice J.; Sasso, Loredana
Abstract: Aim: Develop and test the validity and reliability of MISSCARE Survey‐Ped adapted from previous versions of the MISSCARE Survey, which measures omitted nursing activities and the reasons why they were left undone. Our secondary aim was to pre‐test the construct validity using Exploratory Factor Analysis (EFA). Background: Missed Nursing Care is described as "every care activity necessary for the patient that is not provided or is seriously delayed". Missed Care is correlated with negative patient outcomes, such as mortality and adverse events. Design: A mixed‐mode cross‐sectional survey. Methods: Participants included registered pediatric nurses and nurses working in pediatric wards. This study was conducted between June and September 2017 and consisted of four phases: (a) analysis of existing surveys and item construction; (b) content and face validity; (c) reliability analysis (acceptability for ease of use, Cronbach's alpha for internal consistency and test–retest to measure stability); and (d) construct validity (EFA). Results: The MISSCARE Survey‐Ped consists of two sections: Section A "Missed Nursing Care Activities" (29 items) and Section B "Reasons for Missed Nursing Care Activities" (17 items). The new survey showed good validity properties and effectively identified Missed Nursing Care activities in pediatric settings. Conclusion: The development and validation of the MISSCARE Survey‐Ped made it possible to conduct an objective and standardized study of missed nursing care activities in the field of pediatrics. This new survey offers the opportunity to collect data that enable to design and implement interventions that improve the quality and safety of pediatric nursing.